Síntese, estudos computacionais e avaliação da atividade antifúngica de novos heterociclos tiazóis, tiadiazóis e tiadiazolínicos. - Nereu Junio Cândido Oliveira (2021)
The growing number of opportunistic fungal infections associated with comorbidities that compromise the immunological host defenses, and the emergence of resistance to antifungal drug consolidated in clinical practice, have contributed to the increase in the mortality rate of patients worldwide. Thus, with the aim of finding new therapeutic options for the treatment of fungal infections, novel thiazolylhydrazone and thiadiazole derivatives were designed and synthesized. In addition, HQSAR models were built in order to understand the structure-activity relationship of this class of compounds and to assist in the design of new substances with a high probability of therapeutic success, with the 2q, 58p and 87t models identified with the best predictive capabilities. The synthesis of the heterocycles occurred through a condensation reaction between aldehydes and ketones with thiosemicarbazide, followed by an intermolecular cyclization reaction between the corresponding thiosemicarbazone with one of the following reagents: α-bromo-acetophenones, ethyl-4-chloroacetoacetate, ethyl-2-chloroacetoacetate or acetic anhydride. The obtained heterocycles were evaluated in vitro against fungal species of Candida albicans, C. glabrata, C. parapsilosis, C. tropicalis, C. krusei, C. auris, Cryptococcus neoformans and C. gatti. The thiazolylhydrazones 2a–2d, 2l–2q and 3d stood up for having a broad spectrum of action and high potency, being the substance 3d more active than fluconazole against all fungal species tested.